Races of common bean (Phaseolus vulgaris, Fabaceae) - Singh, S.P.; Gepts, Paul L.; Debouck, Daniel G. (Springer, 1991)
Evidence for genetic diversity in cultivated common bean (Phaseolus vulgaris) is reviewed. Multivariate statistical analysis of morphological, agronomic, and molecular data, as well as other available information on Latin American landraces representing various geographical and ecological regions of their primary centers of domestication in the Americas, reveal the existence of two major groups of germplasm: Middle American and Andean South American, which could be further divided into six races. Three races originated in Middle America (races Durango, Jalisco, and Mesoamerica) and three in Andean South America (races Chile, Nueva Granada, and Peru). Their distinctive characteristics and their relationships with previously reported gene pools are discussed. (AS)